IMPLEMENTASI KEBIJAKAN RETRIBUSI PELAYANAN PASAR DI KABUPATEN SIGI - Rahmawati, Rahmawati (Katalogis, 2015)
This research aimed to find out how the implementation of market service retribution policy of Sigi Regency. The Research employed desciptive qualitative method and the data collected through observation, interview, and documentation. The sample was 7 persons who selected through purposive sampling. The result indicates that the implementation of market service retribution policy of Sigi regency has not been good. By employing implementation model theoryÂ of George Edward III it reveals that some aspect influence it, namely : 1) comunitation of Local Regulagion Contens No. 3 of 2011 concerning Market service Retribution of Sigi Regency have been run weel. 2) Natural resources in imlementattion of local Regulagion Contens No. 3 of 2011 concerning Market Service Retribution of Sigi Regency have not been sufficient. 3) The attitude of policy conductors in Sigi Regency has shown good commitment. 4) Bureaucratic strukture running on the impementation of market service retribution policy of Sigi Regency through standar operational procedure has been doen well.